PENGARUH SISTEM PENGENDALIAN INTERN PEMERINTAH, KINERJA PEGAWAI, PENGAWASAN MELEKAT DAN PENGAWASAN FUNGSIONAL TERHADAP EFEKTIVITAS PENGELOLAAN KEUANGAN DAERAH (Studi pada SKPD Kabupaten Lima Puluh Kota Payakumbuh Sumatra Barat) - Utami, Nindya; Basri, Yessi Mutia; ', Al Azhar L (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aimed to examine the effect of Government Internal Control System, Employee Performance, Monitoring Fitted and functional supervision on the Effectiveness of Financial Management (Studies in SKPD Lima Puluh Kota West Sumatra). This study used convenience sampling method. The sample in this study is the SKPD Lima Puluh Kota West Sumatra. Respondents were instrumental in this research is 75 respondents consisting of a chief financial officer, financial records staff / accounting and regional inspectorate. The statistical method used to test the hypothesis is multiple regression with the help of SPSS version 18.0. The results provide evidence that the Government Internal Control System, Employee Performance, Monitoring and Control Functional Fitted have significant effect on the Effectiveness of Financial Management through multiple correlation coefficient (R) of 0789 and the relationship is very strong.Keywords: Government Internal Control System, Employee Performance, Monitoring, Control Functional Fitted and Fiscal Management Effectiveness